PHBS Health Education in RW 05 Laindeha Village Pandawai District East Nusa Tenggara - Ratu, Jenyati Ndula; Ardayani, Tri; Hotmaida, Linda; Sitorus, Neti; Yogisutanti, Gurdani; Fuadah, Fahmi (CV Media Inti Teknologi, 2025)
This activity aims to plan the community service activities to solve problems obtained based on situation analysis of the priority of problems obtained by providing health education to the community so that they always maintain their health. The implementation of activities that have been carried out by the planned time, namely activities carried out in June-August 2024 which consists of preparation, implementation and closing. Preparations are carried out with various activities, including field surveys, problem identification, approaches to the community, situation analysis, and proposal preparation carried out in July 2024. The implementation will be carried out in August 2024 with preparatory activities for counseling and counseling activities through the delivery of material on PHBS. The closing activity was carried out by preparing a report. The results of the study show that public knowledge about the definition, causes, symptoms, prevention, treatment, and impact of PHBS has increased. This community service activity is expected to bring real benefits to the people of Laindeha village and become an inspiration for similar efforts in various regions.